PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN PADA PT FIFGROUP CABANG RANGKASBITUNG - Muhi Mukti; Enong Komala (The Asia Pacific Journal Of Management Studies, 2020)
In general, the problems of incentives and performance are interrelated, because in fact there are several companies or agencies and organizations found in the phenomenon of a decrease in employee performance which is caused by dissatisfaction in receiving incentives provided. It becomes natural when we associate with the number of life needs of employees who are very many, then it is natural if there is an employee demand for the provision of incentives with a satisfactory value. Maybe this way employees will be able to improve their performance, even though the estimate does not necessarily ensure the attitude of empolyees who will work. The method in this study is to use a quantitative descriptive method case study approach that uses descriptive design that is by solving a case of empolyee performance On PT Fifgroup Branc Rangkasbitung. While the sample in the study was 40 people taken from the entire population of 100While the results of the study note that incentives have a positive relationship to employee performance, it is known from the results of the hypothesis test where α 0,05 ≥ from the significance of 0,001 it can be concluded that there is a significant relationship between incentives and employee performance. As for the conclusions that the writer can give in this study is based on the results of research conducted by referrring to the respondents, answers, it is known that the application of incentives that have been felt is quite satisifed or fulfilling the wishes of employees. While the performance of employees has shown a good level which includes the opportunity to progress, and receive incentives for work morale.While the advice that the author gives in this research is one of the ways that the company can do to maximize employee performance is to provide good encouragement to employees, both material and non-material. And one way that can be done is to provide incentives to employees, and in its application depends on the company’s policies.